Adiposity and binge eating are related to liking and wanting for food in Brazil: A cultural adaptation of the Leeds food preference questionnaire. (1st February 2019) - Carvalho-Ferreira, Joana Pereira de; Finlayson, Graham; da Cunha, Diogo Thimoteo; Caldas, Gabriele; Bandoni, Daniel; de Rosso, Veridiana Vera
Abstract: The Leeds Food Preference Questionnaire (LFPQ) measures separable psychological components of food reward (Liking and Wanting). In this study a cultural adaptation of the LFPQ for a Brazilian population (LFPQ-BR) was examined by comparing liking and wanting scores in fasted and fed states and their association with adiposity and disturbed eating. A culturally adapted food picture database was validated by an online questionnaire completed by 162 individuals. Cluster analysis verified if the foods were accurately perceived in terms of sweetness, fat and calorie content. Subsequently, 48 male (N = 21) and female (N = 27) adults with mean Body Mass Index 26.6 (0.9) kg/m 2, and mean age 32.8 (1.4) years, were evaluated by the LFPQ-BR before and after a fixed test meal. The Binge Eating Scale was used to measure binge eating symptoms. There was a decrease in explicit liking, implicit wanting, and explicit wanting scores for food in general in the fed condition. The implicit and explicit wanting and explicit liking scores for high-and-low fat savoury food decreased and for high-and-low fat sweet foods increased to a greater extent after the savoury test meal. Body Mass Index was found to predict implicit wanting for high fat relative to low fat foods. Binge eating symptoms predicted high fat sweet explicit liking and explicit wanting in the fed condition. Finally, high fat sweet preference was found to be sex-related as females had greater implicit wanting for high fat sweet foods in fasted and fed states. The results presented here indicate that the LFPQ-BR is a useful instrument for the evaluation of liking and wanting for food in Brazil.